Trakeostomi Dilatasi Perkutan dengan Bimbingan Ultrasonografi Waktu Nyata pada Pasien Kritis III: Laporan Kasus - Rikardi, Fachrizal; Adiyanto, Bowo (PT Kalbe Farma Tbk., 2025)
Introduction: Tracheostomy is a common procedure in intensive care units for critically ill patients with mechanical ventilation. Case: This case report describes the use of real-time ultrasonography (USG) guidance for percutaneous dilatational tracheostomy (PDT) in a 63-year-old female with prolonged mechanical ventilation following craniotomy. The patient had relative contraindications including short neck and morbid obesity (BMI 40.8). On day 7 of ICU admission, a PDT was successfully performed using real-time ultrasonography (USG) guidance. USG was utilized to identify key anatomical landmarks, such as tracheal rings and vascular structures, ensuring safe and accurate needle placement. The use of real-time USG significantly reduced the risk of complications including hemorrhage, tracheal injury, or pneumothorax. The procedure was completed without incident, and the patient showed clinical improvement post-intervention, including enhanced respiratory function and gradual weaning from mechanical ventilation. Conclusion: This report highlights the safety and efficacy of USG-guided PDT, especially in high-risk patients with difficult neck anatomy. It also underlines the importance of ultrasound as a widely available and cost-effective tool in ICU settings. The case supports further implementation of real-time USG-guided techniques in percutaneous tracheostomy to improve procedural success and patient outcomes. Further research involving a larger cohort is needed to establish standardized protocols and evaluate long-term outcomes of this approach.